Review of Structure Types and New Development Prospects of Artificial Reefs in China - Pan, Yun; Tong, Huanhuan; Wei, Dongze; Xiao, Weiqi; Xue, Dawen (Frontiers in Marine Science, 2022)
Artificial reefs are beneficial to restore fishery resources and increase fishery production. Meanwhile, they play a significant role in improving ocean ecology and accelerating the evolution of fishery industries. Since they are generally affected by currents, waves, and other hydrological factors, the flow field around artificial reefs and their stabilities have become a research hotspot in recent years. Research on artificial reefs is a systematic process consisting of four aspects: Firstly, the significance, the definition, the mechanism, and the present research progress were introduced for artificial reefs in detail. Secondly, the development trend of the sit-bottom artificial reef and that of the floating artificial reef were summarized, respectively. Thirdly, it was found that the combination of traditional artificial reefs and emerging ocean engineering has a great development potential in practical engineering. Finally, the existing problems related to the hydrodynamic characteristics of the artificial reefs in China were summarized, and the prospects of artificial reefs were proposed. The purpose of this study is to provide a scientific reference for the ecological and sustainable development of the large-scale construction of artificial reefs in the ocean.